2023
DOI: 10.3390/nu15153311
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dietary Acid Load Might Be a Potent Derivative Factor for Multiple Sclerosis: The Results from a Case–Control Study

Abstract: This study aimed to investigate the association between dietary acid load (DAL) and multiple sclerosis (MS), through the potential renal acid load (PRAL) and net endogenous acid production (NEAP) scores. In a hospital-based case–control study of 109 patients with MS and 130 healthy individuals, a validated 168-item semi-quantitative food frequency questionnaire and a logistic regression model were used to evaluate the association between the DAL and MS. After adjusting for age (years), gender (male/female), bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…According to Keykhaei et al, [ 2 ] consuming a diet rich in fruits, vegetables, salads, stews, bread, and low-fat dairy can lower the risk of MS. Additionally, Saeedirad et al [ 23 ] found that a higher intake of plant-based protein can reduce the risk of MS. In contrast, food items with high levels of saturated fatty acids were linked to a greater risk of MS than those rich in fiber.…”
Section: Discussionmentioning
confidence: 99%
“…According to Keykhaei et al, [ 2 ] consuming a diet rich in fruits, vegetables, salads, stews, bread, and low-fat dairy can lower the risk of MS. Additionally, Saeedirad et al [ 23 ] found that a higher intake of plant-based protein can reduce the risk of MS. In contrast, food items with high levels of saturated fatty acids were linked to a greater risk of MS than those rich in fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals possess potent antioxidant and anti-inflammatory properties that may counteract the oxidative stress and chronic inflammation central to MS pathogenesis [ 10 , 15 , 16 ]. Conversely, a diet high in acid-promoting animal protein sources and low in alkaline plant foods may contribute to a state of low-grade metabolic acidosis, which can promote inflammation, insulin resistance, and other metabolic disturbances implicated in the development and progression of MS [ 11 , 12 , 17 20 ].…”
Section: Introductionmentioning
confidence: 99%